Catalyst, method for producing catalyst, hydrogen generator, and fuel cell system

The catalyst, featuring a mother nucleus of iron-containing layered double hydroxides and a tripod-type ligand, addresses the inefficiency in hydrogen generation from ammonia borane by enhancing surface area and iron ratio, resulting in improved hydrogen generation efficiency.

JP2025046704APending Publication Date: 2025-04-02DENKA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023154945
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

Existing technologies for generating hydrogen from hydrogen storage compounds like ammonia borane are not efficient, leaving room for improvement.

Method used

A catalyst comprising a mother nucleus with interlayer anions and water molecules, primarily made of iron-containing layered double hydroxides, and a tripod-type ligand with three hydrophilic groups coordinated on the surface, enhancing hydrogen generation efficiency from boron hydride salts.

Benefits of technology

The catalyst achieves efficient hydrogen generation from boron hydride salts by increasing the BET specific surface area and optimizing the atomic ratio of iron, leading to improved contact area and reaction efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025046704000001_ABST
    Figure 2025046704000001_ABST
Patent Text Reader

Abstract

To provide: a catalyst having excellent hydrogen generation efficiency and a method for producing the same, a hydrogen generator comprising the catalyst, and a fuel cell system comprising the hydrogen generator.SOLUTION: According to one aspect of the present invention, provided is a catalyst used to generate hydrogen from a borohydride salt. The catalyst comprises: a core that has interlayer anions and interlayer water molecules and that includes, as the main component, a layered double hydroxide containing iron; and a tripod ligand that is coordinated on the surface of the core, with three hydrophilic groups located on the core side.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst, a method for producing the catalyst, a hydrogen generating device, and a fuel cell system. [Background technology]

[0002] It has been shown that a layered double hydroxide called Green Rust (GR) can generate hydrogen from a hydrogen storage compound such as ammonia borane (see Patent Document 1). However, Patent Document 1 does not fully consider how to increase the efficiency of generating hydrogen from a hydrogen storage compound, and there is room for further improvement. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2022-80364 A Summary of the Invention [Problem to be solved by the invention]

[0004] In view of the above circumstances, the present invention provides a catalyst excellent in hydrogen generation efficiency and a method for producing the same, a hydrogen generation device including the catalyst, and a fuel cell system including the hydrogen generation device. [Means for solving the problem]

[0005] According to one aspect of the present invention, there is provided a catalyst for generating hydrogen from a borohydride salt, the catalyst comprising a mother core having an interlayer anion and an interlayer water molecule and containing an iron-containing layered double hydroxide as a main component, and a tripod ligand coordinated to the surface of the mother core with three hydrophilic groups on the mother core side.

[0006] According to this embodiment, hydrogen can be efficiently generated from borohydride salt. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a process diagram showing one embodiment of a method for producing a catalyst of the present invention. [Diagram 2] 1 is a schematic diagram showing the configuration of one embodiment of a hydrogen generation device of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, embodiments of the present invention will be described. Various features shown in the following embodiments can be combined with each other. The catalyst of the present invention is a catalyst used to generate hydrogen from a borohydride salt. Examples of the borohydride salt include sodium borohydride, potassium borohydride, magnesium borohydride, lithium borohydride, and ammonia borane. These borohydride salts may be used alone or in combination of two or more.

[0009] This catalyst has an interlayer anion and an interlayer water molecule, and is provided with a mother core containing an iron-containing layered double hydroxide (LDH) as a main component, and a tripod ligand coordinated to the mother core surface with three hydrophilic groups on the mother core side. A catalyst having such a composition can efficiently generate hydrogen from borohydride salt. The presence of a tripod ligand coordinated to the surface of the mother nucleus can be, for example, 13 This can be confirmed by C CP / MAS NMR measurement, FTIR measurement, etc. In this specification, the term "main component" refers to the component that is contained in the largest amount when multiple components are contained. Components other than the "main component" are referred to as "minor components". The mother nucleus may consist only of the layered double hydroxide that is the main component, or may contain a minor component different from the main component.

[0010] In addition, the crystal growth of the core formed during the production (synthesis) of the catalyst is suppressed by the coordination of tripod ligands on the surface of the core, and as a result, the catalyst particles become finer, and the BET specific surface area tends to increase. The three hydrophilic groups may be, independently of one another, hydroxyl, amino, aldehyde, carboxyl, thiol, phosphino, amide, etc., but are preferably hydroxyl or amino. These substituents are preferred because they have a high affinity with the layered double hydroxide (nucleus), particularly with the iron (iron ion) contained in the layered double hydroxide. Therefore, such substituents can also be called iron affinity groups.

[0011] In addition, the tripod ligand may have other substituents in addition to the three hydrophilic groups. When the tripod ligand has other substituents, steric hindrance occurs between the molecules of the tripod ligand, making it easier for the tripod ligand to be coordinated to the mother nucleus. This tends to make the catalyst particles finer. The other substituents are preferably amino groups or alkyl groups having 1 to 2 carbon atoms. Specific examples of such tripodal ligands include tris(hydroxymethyl)aminomethane (THAM), 1,1,1-tris(hydroxymethyl)ethane, tris(2-aminoethyl)amine, 1,1,1-tris(hydroxymethyl)ethane, and 1,1,1-tris(hydroxymethyl)propane.

[0012] The specific value of the BET specific surface area of ​​the catalyst is 60m 2 / g or more 300m 2 / g or less, and 2 / g or more 250m 2 / g or less, and 2 / g or more 200m 2 It is more preferable that the molecular weight is about 1 / g or less. In this way, a catalyst having a high BET specific surface area can increase the contact area with borohydride salts (borohydride or its ions), and therefore can further increase the efficiency of hydrogen generation from borohydride salts. Even if the BET specific surface area of ​​the catalyst is increased beyond the above upper limit, no further increase in effect can be expected, and it is also troublesome to produce a catalyst having such a large BET specific surface area. The BET specific surface area of ​​this catalyst can be measured by the BET single-point method using nitrogen gas in accordance with JIS Z 8830:2013 "Method for measuring specific surface area of ​​powder (solid) by gas adsorption."

[0013] The crystallite size of the layered double hydroxide is preferably about 15 nm or less, more preferably about 0.1 nm to 10 nm, and even more preferably about 1 nm to 5 nm. The core containing the layered double hydroxide having such a relatively small crystallite size is easily made fine. Therefore, the catalyst tends to have a larger BET specific surface area. The crystallite size of this layered double hydroxide can be measured by X-ray diffraction method (XRD method).

[0014] The layered double hydroxide contains trivalent iron and divalent iron, and the atomic ratio of trivalent iron to the total of trivalent iron and divalent iron is preferably about 0.75 or less, more preferably about 0.4 to 0.7, and even more preferably about 0.5 to 0.6. In this case, the layered double hydroxide obtained forms a structure resembling fine petals open, or a structure resembling an assembly of irregularly shaped (irregular) particles. In other words, the layered double hydroxide has a tendency to easily become finer. This increases the BET specific surface area of ​​the catalyst, and can increase the efficiency of hydrogen generation from borohydride salts. This atomic ratio can be determined by Mossbauer spectrometry. According to the investigations of the present inventors, it is believed that the layered double hydroxide having the above structure is formed due to the relatively high content of divalent iron, the use of a tripodal ligand, and other factors. Moreover, a catalyst having the above-mentioned BET specific surface area and atomic ratio can be suitably produced by the catalyst production method described below.

[0015] Examples of interlayer anions include carbonate ions, lactate ions, chloride ions, and sulfate ions. Of these, it is preferable that the interlayer anions include at least one of carbonate ions and lactate ions. These interlayer anions include boron hydride (BH3 in the case of ammonia borane) generated from borohydride salts or its ions (BH4 - It is easily exchanged with sodium borohydride, etc., and boron hydride or its ions are easily incorporated between the layers where water molecules exist. This makes it possible to further increase the efficiency of hydrogen generation through the hydrolysis reaction (reaction with water molecules) of boron hydride or its ions. The layered double hydroxide preferably has the general formula: [Fe II 1-x Fe III x (OH)2] x+ (x / n)[A n- ] x- m[H2O] (where A n- is an interlayer anion, and H2O is an interlayer water molecule.

[0016] The above-mentioned catalyst is produced by the following catalyst production method: Hereinafter, one embodiment of the catalyst production method of the present invention will be described. FIG. 1 is a process diagram showing one embodiment of the method for producing a catalyst of the present invention. The method for producing the catalyst shown in FIG. 1 includes a step of preparing raw materials for forming a mother nucleus and a tripodal ligand (step S1), a step of obtaining a mixed solution by mixing the raw materials and the tripodal ligand (step S2), a step of forming a mother nucleus by hydrothermal synthesis of the raw materials in the mixed solution and coordinating the tripodal ligand to the surface of the mother nucleus with three hydrophilic groups on the mother nucleus side to obtain a catalyst (step S3), a step of removing the solvent to recover the catalyst (step S4), a step of washing the catalyst (step S5), and a step of drying the catalyst (step S6). Each step will be described below in order.

[0017] (Process S1) In this step S1, a divalent iron salt and a nucleating agent as raw materials for forming a mother nucleus, a tripod ligand, and a reducing solvent as a solvent are prepared. Here, various salts containing divalent iron can be used as the divalent iron salt. Among them, the divalent iron salt is preferably at least one selected from the group consisting of FeCl2, Fe(NO3)2, FeSO4, and Fe(CH3COO)2. By using such a divalent iron salt, it is easy to produce a layered double hydroxide (catalyst) that is stable and does not deteriorate over time. In addition, according to the inventors' investigation, the BET specific surface area of ​​the catalyst tends to be large, although the reason is unclear. The divalent iron salt is preferably a hydrate. By using such a divalent iron salt, it is easy to produce a layered double hydroxide (catalyst) having the above-mentioned properties. If necessary, a trivalent iron salt may be used alone instead of the divalent iron salt, or a divalent iron salt and a trivalent iron salt may be used in combination. The trivalent iron salt is preferably at least one selected from the group consisting of FeCl3, Fe(NO3)3, Fe2(SO4)3, and Fe(OH)(CH3COO)2.

[0018] The nucleating agent is not particularly limited, but it is preferable to use at least one selected from the group consisting of sodium acetate (CH3COONa), potassium acetate (CH3COOK), and sodium acetate trihydrate (CH3COONa 3H2O). By using such a nucleating agent, it is easy to produce a layered double hydroxide (catalyst) that is stable and does not deteriorate over time. The reducing solvent is not particularly limited, but it is preferable to use, for example, glycerol or ethylene glycol. By using these reducing solvents, lactate ions can be easily introduced as interlayer anions into the layered double hydroxide. The reducing solvent may contain water.

[0019] The mixing ratio of the iron salt (divalent iron salt and / or trivalent iron salt) to the nucleating agent is preferably about 100:50 to 100:500 in molar ratio, more preferably about 100:100 to 100:400 in molar ratio, and even more preferably about 100:150 to 100:300 in molar ratio. In this case, the layered double hydroxide (catalyst) can be produced smoothly and reliably. The mixing ratio of the iron salt (divalent iron salt and / or trivalent iron salt) and the tripod ligand contained in the raw material is preferably about 100:50 to 100:2000 in molar ratio, more preferably about 100:75 to 100:1500, and even more preferably about 100:100 to 100:1000. In this case, the particles of the layered double hydroxide (catalyst) can be easily made fine.

[0020] (Process S2) In this step S2, the iron salt, the nucleating agent, the tripod ligand, and the reducing solvent are mixed substantially simultaneously to prepare a mixed solution. When the iron salt and the nucleating agent are mixed separately into the solvent, pre-heating is required before the hydrothermal synthesis. However, since the iron salt, the nucleating agent, and the tripod ligand are mixed into the solvent at once, the hydrothermal synthesis can be performed without pre-heating, and therefore the number of steps can be reduced. In addition, since the iron salt and the nucleating agent (and some tripod ligands as well) are not dissolved but are suspended in the mixed solution, the mixed solution is also called a suspension. (Process S3) In this step S3, the raw materials are reacted in the mixed liquid by hydrothermal synthesis to obtain a catalyst. Here, the hydrothermal synthesis is preferably carried out in a state where the mixed liquid is contained in a sealed container. In this case, it is possible to prevent oxygen from being continuously supplied to the mixed liquid from the external environment. As a result, it is possible to reduce the amount of divalent iron that is oxidized and converted to trivalent iron. This makes it possible to make the catalyst particles finer, increase the BET specific surface area, and also increase the amount of divalent iron contained in the catalyst.

[0021] The temperature in the hydrothermal synthesis is preferably about 50° C. or higher and about 350° C. or lower, more preferably about 150° C. or higher and about 250° C. or lower, and even more preferably about 150° C. or higher and 250° C. or lower. By carrying out the hydrothermal synthesis within such a temperature range, it is possible to efficiently produce a layered double hydroxide (catalyst), and to prevent structural changes in the layered double hydroxide and alteration and deterioration of the solvent, thereby producing a high-quality layered double hydroxide. The time for the hydrothermal synthesis is preferably about 0.5 to 50 hours, more preferably about 1 to 40 hours, and even more preferably about 1.5 to 30 hours. By carrying out the hydrothermal synthesis within such a time range, a sufficient amount of layered double hydroxide (catalyst) can be produced.

[0022] (Process S4) In this step S4, the solvent is removed from the mixed liquid after the hydrothermal synthesis to recover the catalyst. The solvent can be removed by, for example, filtration, suction filtration, decantation, centrifugation, or the like. (Process S5) In this step S5, the recovered catalyst is washed with a washing liquid. Examples of the cleaning liquid include water (distilled water, ultrapure water, RO water, etc.), alcohols (ethanol, etc.), ketones (acetone, etc.), etc. These may be used alone or in combination of two or more. (Process S6) In this step S6, the catalyst is dried. The catalyst can be suitably dried by, for example, natural drying, heat drying, blow drying, vacuum drying, or the like.

[0023] Next, an embodiment of the hydrogen generating device of the present invention will be described. The hydrogen generating device includes a catalyst and a borohydride salt. FIG. 2 is a schematic diagram showing the configuration of one embodiment of the hydrogen generation device of the present invention. The hydrogen generation device 1 shown in Fig. 2 has a bottomed cylindrical container 2. A partition wall 3 is provided midway in the height direction of the container 2, and the space within the container 2 is divided into an upper space 2a and a lower space 2b. In the upper space 2a, a solid borohydride salt is accommodated on the partition wall 3. In addition, in the lower space 2b, a mixture of a catalyst and water is accommodated. A lid 4 is attached to the container 2 so as to close the upper opening, and a piston 5 is disposed on the borohydride salt contained in the upper space 2a.

[0024] A compressed spring (biasing member) 6 is disposed between the lid 4 and the piston 5. As a result, the borohydride salt is biased (pressed) downward by the piston 5. The vessel 2 is provided with an injection port 21 communicating with the upper space 2a and an exhaust gas port 22 communicating with the lower space 2b. In addition, a discharge port 31 communicating with the upper space 2a is provided in the center of the partition wall 3. The injection port 21 and the lower space 2b are connected by a line L, and a filter (not shown) and a pump P are provided in this line L in this order from the lower space 2b side.

[0025] According to this configuration, when the water in the mixed liquid is supplied from the lower space 2b to the upper space 2a via the line L and the injection port 21 by operating the pump P, the borohydride salt dissolves in the water. The water in which the borohydride salt is dissolved is returned to the lower space 2b through the exhaust port 31 and supplied to the mixed liquid. As a result, hydrogen is generated from borohydride or its ions due to the action of the catalyst in the mixed liquid. The generated hydrogen is exhausted from the hydrogen generation device 1 through the exhaust gas port 22. The reaction between the borohydride salt and the catalyst is sufficiently promoted by irradiation with sunlight, but a light source may be provided on the outer periphery of the container 2 to irradiate the mixed liquid contained in the lower space 2b with light of a specific frequency wavelength.

[0026] In addition, the reaction between the borohydride salt and the catalyst proceeds sufficiently even at room temperature (25° C.), which has the advantage that hydrogen can be generated from the borohydride salt at low cost. The fuel cell system of the present invention is provided by combining such a hydrogen generation device 1 with a fuel cell. That is, one embodiment of the fuel cell system of the present invention includes the hydrogen generation device 1 and a fuel cell that generates power by using hydrogen generated in the hydrogen generation device 1. The catalyst, the method for producing a catalyst, the hydrogen generation device, and the fuel cell system of the present invention have been described above, but the catalyst, the method for producing a catalyst, the hydrogen generation device, and the fuel cell system of the present invention are not limited to the above-described embodiments. Furthermore, it may be provided in the following aspects:

[0027] (1) A catalyst used for generating hydrogen from a borohydride salt, comprising: a mother nucleus having an interlayer anion and an interlayer water molecule and containing an iron-containing layered double hydroxide as a main component; and a tripod ligand coordinated to the surface of the mother nucleus with three hydrophilic groups on the mother nucleus side.

[0028] (2) The catalyst according to the above (1), wherein the interlayer anion includes at least one of a carbonate ion and a lactate ion.

[0029] (3) The catalyst according to the above (1) or (2), wherein the three hydrophilic groups are, independently of one another, a hydroxyl group or an amino group.

[0030] (4) The catalyst according to any one of the above (1) to (3), wherein the tripod ligand further has an amino group or an alkyl group having 1 to 2 carbon atoms in addition to the three hydrophilic groups.

[0031] (5) In the catalyst according to any one of (1) to (4) above, the BET specific surface area of ​​the catalyst is 60 m 2 / g or more 300m 2 / g or less of a catalyst.

[0032] (6) The catalyst according to any one of the above (1) to (5), wherein the layered double hydroxide has a crystallite size of 15 nm or less.

[0033] (7) A method for producing the catalyst according to any one of (1) to (6) above, comprising the steps of: preparing raw materials for forming the mother nucleus, the raw materials including an iron salt, and the tripodal ligand; obtaining a mixed solution by mixing the raw materials and the tripodal ligand; and forming the mother nucleus by hydrothermal synthesis of the raw materials in the mixed solution, and coordinating the tripodal ligand to a surface of the mother nucleus with the three hydrophilic groups on the mother nucleus side, thereby obtaining the catalyst.

[0034] (8) The method for producing a catalyst according to (7) above, wherein the mixing ratio of the iron salt and the tripod ligand contained in the raw material is 100:50 or more and 100:2000 or less in terms of molar ratio.

[0035] (9) The method for producing a catalyst according to the above (7) or (8), wherein the hydrothermal synthesis is carried out in a state where the mixed liquid is contained in a sealed container.

[0036] (10) The method for producing a catalyst according to any one of the above (7) to (9), wherein the temperature in the hydrothermal synthesis is 50° C. or higher and 350° C. or lower.

[0037] (11) The method for producing a catalyst according to any one of the above (7) to (10), wherein the time for the hydrothermal synthesis is 0.5 hours or more and 50 hours or less.

[0038] (12) A hydrogen generating device comprising the catalyst according to any one of (1) to (6) above and a borohydride salt.

[0039] (13) A fuel cell system comprising: the hydrogen generation device according to (12) above; and a fuel cell that generates electricity using hydrogen generated by the hydrogen generation device. Of course, this is not the case.

[0040] Finally, although various embodiments according to the present disclosure have been described, these are presented as examples and are not intended to limit the scope of the invention. The novel embodiment can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. The embodiments and their modifications are included within the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims. EXAMPLES

[0041] The present invention will be described in more detail below using the following examples and comparative examples, but the present invention is not limited to the following examples.

[0042] 1. Catalyst Preparation Example 1 First, 1 mol of FeCl2·4H2O (iron salt), 3 mol of sodium acetate (nucleating agent), 3 mol of tris(hydroxymethyl)aminomethane (THAM: tripod ligand), and 82 mol of glycerol (reducing solvent) were prepared. Next, these were put into a sealed polytetrafluoroethylene container and mixed to obtain a mixed solution. Note that FeCl2·4H2O was ground in a mortar before use.

[0043] The container was kept sealed, and the mixture was heated at 200°C for 24 hours. As a result, a layered double hydroxide (nucleus) was formed in the mixture through hydrothermal synthesis of FeCl2·4H2O and sodium acetate, and tris(hydroxymethyl)aminomethane was coordinated to its surface to obtain a catalyst. Thereafter, the mixture after the hydrothermal synthesis was centrifuged to recover the catalyst. Next, the recovered catalyst was washed twice with 20 mL of ethanol, once with 20 mL of a washing solution prepared by mixing pure water and ethanol at a volume ratio of 1:1, and once with 20 mL of ethanol. Finally, the washed catalyst was dried at 80° C. for 24 hours. Through the above steps, the catalyst of Example 1 was obtained.

[0044] Example 2 A catalyst of Example 2 was produced in the same manner as in Example 1, except that the time for hydrothermal synthesis was changed to 2 hours. Example 3 A catalyst of Example 3 was produced in the same manner as in Example 1, except that the amount of tris(hydroxymethyl)aminomethane mixed was changed to 12 mol. Example 4 A catalyst of Example 4 was produced in the same manner as in Example 3, except that the time for hydrothermal synthesis was changed to 2 hours.

[0045] Example 5 A catalyst of Example 5 was produced in the same manner as in Example 1, except that tris(hydroxymethyl)aminomethane was changed to 1,1,1-tris(hydroxymethyl)ethane. Example 6 A catalyst of Example 6 was produced in the same manner as in Example 1, except that tris(hydroxymethyl)aminomethane was changed to tris(carboxymethyl)amine. Example 7 The catalyst of Example 7 was produced in the same manner as in Example 1, except that FeCl2·4H2O (divalent iron salt) was changed to FeCl3 (trivalent iron salt). (Comparative Example) A catalyst of Comparative Example 1 was produced in the same manner as in Example 1, except that the mixing of tris(hydroxymethyl)aminomethane was omitted.

[0046] 2. Measurement and Evaluation 2-1.BET specific surface area The catalysts obtained in each of the Examples and Comparative Examples were subjected to measurement of the BET specific surface area in accordance with JIS Z 8830:2013 "Method for measuring the specific surface area of ​​powder (solid) by gas adsorption." The BET specific surface areas are shown in Tables 1 and 2 below.

[0047] 2-2.XRD measurement The catalysts obtained in each of the Examples and Comparative Examples were subjected to XRD measurement using an XRD measuring device (manufactured by Rigaku Corporation, "Ulitima IV"). The crystallite sizes calculated based on the full width at half maximum of the peaks observed in this XRD measurement are shown in Tables 1 and 2.

[0048] 2-3. Measurement of the atomic ratio of iron The catalysts (layered double hydroxides) obtained in each of the Examples and Comparative Examples were subjected to Mössbauer spectroscopy. 57 The Mössbauer spectrum of Fe was measured. The atomic ratio of trivalent iron to the total of trivalent iron and divalent iron estimated by this Mössbauer spectroscopy is shown in Tables 1 and 2.

[0049] 2-4.SEM photography The catalysts obtained in each of the Examples and Comparative Examples were photographed using a scanning electron microscope (manufactured by JEOL, "JSM-7001F / SHL") at a magnification of 30,000 times to obtain SEM images. The SEM images are shown in Tables 1 and 2.

[0050] 2-6. Hydrogen generation test First, a mixed powder of 6.0 mg of the catalyst obtained in each of the Examples and Comparative Examples and 6.0 mg of sodium borohydride (SBH) was placed in a test tube and mixed. Next, the inside of the test tube was replaced with argon gas for 1 minute, and then 3.0 mL of water was added to the mixed powder, and the amount of hydrogen generated within 10 minutes was measured. The amount of hydrogen generated was measured by gas chromatography analysis. When no catalyst was used, almost no hydrogen was generated, and the amount of hydrogen generated was substantially 0 μmol. The results are also shown in Tables 1 and 2.

[0051] [Table 1]

[0052] [Table 2]

[0053] As shown in the SEM images in Tables 1 and 2, the catalyst particles of each Example formed a structure resembling fine open petals, a structure resembling an aggregation of irregularly shaped (irregular) particles, etc. In contrast, the catalysts of the Comparative Examples formed a structure in which fine spherical particles were attached to the surface of columnar particles, or a structure of columnar particles with no fine spherical particles attached to the surface. It was also confirmed that the amount of hydrogen generated could be changed by adjusting the BET specific surface area. [Explanation of symbols]

[0054] 1: Hydrogen generator 2: Container 2a: Upper space 2b: Lower space 21: Injection port 22: Exhaust gas port 3: Bulkhead 31: Discharge port 4: Lid 5: Piston 6: Spring L: Line P: Pump S1: Process S2: Process S3: Process S4: Process S5: Process S6: Process

Claims

1. A catalyst for use in generating hydrogen from a borohydride salt, comprising: A mother core having an interlayer anion and an interlayer water molecule and containing an iron-containing layered double hydroxide as a main component; A catalyst comprising: a tripod ligand coordinated to the surface of the mother nucleus with three hydrophilic groups on the mother nucleus side.

2. The catalyst according to claim 1, The interlayer anion comprises at least one of a carbonate ion and a lactate ion.

3. The catalyst according to claim 1, The three hydrophilic groups are, independently of each other, hydroxyl groups or amino groups.

4. The catalyst according to claim 1, A catalyst, wherein the tripod ligand further has an amino group or an alkyl group having 1 to 2 carbon atoms in addition to the three hydrophilic groups.

5. The catalyst according to claim 1, The BET specific surface area of ​​the catalyst is 60 m 2 / g or more 300m 2 / g or less.

6. The catalyst according to claim 1, A catalyst, wherein the layered double hydroxide has a crystallite size of 15 nm or less.

7. A method for producing the catalyst according to any one of claims 1 to 6, comprising the steps of: preparing a raw material for forming the mother nucleus, the raw material including an iron salt, and the tripod ligand; a step of obtaining a mixed solution by mixing the raw material and the tripod ligand; forming the mother nucleus by hydrothermal synthesis of the raw materials in the mixed liquid, and coordinating the tripod ligand to a surface of the mother nucleus with the three hydrophilic groups on the mother nucleus side, thereby obtaining the catalyst.

8. The method for producing a catalyst according to claim 7, A method for producing a catalyst, wherein a mixing ratio of the iron salt and the tripod ligand contained in the raw material is 100:50 or more and 100:2000 or less in terms of a molar ratio.

9. The method for producing a catalyst according to claim 7, The hydrothermal synthesis is carried out in a state where the mixed liquid is contained in a sealed container.

10. The method for producing a catalyst according to claim 7, The method for producing a catalyst, wherein the temperature in the hydrothermal synthesis is 50° C. or higher and 350° C. or lower.

11. The method for producing a catalyst according to claim 7, The method for producing a catalyst, wherein the hydrothermal synthesis time is 0.5 hours or more and 50 hours or less.

12. 1. A hydrogen generating apparatus comprising: The catalyst according to any one of claims 1 to 6, and a borohydride salt.

13. 1. A fuel cell system comprising: The hydrogen generating apparatus according to claim 12 ; a fuel cell that generates electricity using the hydrogen generated in the hydrogen generation device.

Citation Information

Patent Citations

  • Green rust, production method thereof, pigment, and anion exchanger

    JP2022080364A